Odpowiedzi

Najlepsza Odpowiedź!
2010-01-04T00:25:15+01:00
A)f(x)=2x²-x² +3=x²+3
f(x)=f(-x)
f(-x)=x²+3 f. jest parzysta

f(x)=-f(-x)
-f(-x)=-(x²+3) nie jest nieparzysta

b) f(x)= -x²÷x⁴+1 = (-1/x²) +1= (-1+x²)/x²
f(-x)= (-1+x²)/x² funkcja parzysta

-f(-x)= -(-1+x²)/x² nie jest nieparzysta
____________________________________________________________

y=(x²-4)/(x²-4x+4)

Df: x²-4x+4≥0
Δ=16-4*1*4=0

x1= 4/2=2

x∈R- {2}
_____________________

y=(x²-4)/(x²-4x+4)
y=(x²-4)/(x-2)²
y=[(x-2)(x+2)] / (x-2)(x-2)
y=(x+2)/(x-2)

x+2=0
x₀=-2